Glomerulonephritis associated with marginal zone B-cell lymphoma: clinical, pathological characteristics of renal injury and treatment (clinical cases) - B. T. Dzhumabaeva; L. S. Birukova; E. P. Golitsyna; V. A. Varshavskiy; U. L. Julhakyan; L. S. Roshchina (Онкогематология, 2015)
Glomerulonephritis associated with marginal zone B-cell lymphoma at the onset of disease is rarely diagnosed. In this article we reported two patient of the extranodal marginal zone B-cell lymphoma with kidney damage. The first patient with the extranodal marginal zone B-cell lymphoma involved the stomach, lymph nodes, bone marrow and associated with mesangioproliferative glomerulonephritis and renal failure. The second patient with the splenic form of marginal zone B-cell lymphoma associated with fibrillary glomerulonephritis and hepatitis C and involve the lymph nodes, liver, bone marrow, and synthesis monoclonal immunoglobulin (IgMκ), cryoglobulin type II. Glomerulonephritis of the both cases were established on the renal biopsies by the morphological investigation, immunofluorescence, and electron microscopy.Both patients received therapy with bendamustine and rituximab, which has resulted in complete remission for lymphatic tumors and improve of kidney function. Overall and event-free survival in the first case corresponds to 21 and 16 months, the second 29 and 20, respectively.These cases illustrates that the kidney may be initially involved by extranodal marginal zone B-cell lymphoma, and the need for expanded investigation of the possible dissemination. Combination of bendamustine and rituximab were effective and safety treatment in these cases.